Legal Assessment of Default in Treaty Law from the Perspective of Contractual Freedom on the Protection of the Parties' Rights - Dahris Siregar (Rechtenstudent, 2026)
The concept of contract freedom is one of the cornerstones of treaty law, which has its roots in economic liberalism. Analyzing the connection between default and the freedom of contract concept in Indonesian treaty law is the goal of this study. As long as the agreement does not violate the law, public order, or decency, the parties are free to form agreements that serve their interests under the freedom of contract concept. But in reality, defaults often lead to disagreements and issues with the parties' rights being protected. This research examines how default is seen in the context of contract freedom and the degree to which the law offers the parties assurance and fairness using a normative juridical technique with a conceptual and legislative approach. The study's results demonstrate that while the principle of freedom of contract affords considerable latitude to contracting parties in establishing the terms of their agreements, predicated on the principle of pacta sunt servanda, these freedoms are nevertheless circumscribed by considerations of public policy, morality, and legal stipulations designed to preclude exploitation and inequity. The study's findings indicate that the principle of freedom of contract is not unqualified, but rather is circumscribed by legal standards governing the legal ramifications of breach of contract. Therefore, the safeguarding of the parties' rights must be appropriately balanced to prevent the misuse of the principle of freedom of contract, while still ensuring the fulfillment of the agreement's intended purpose.